The Input Communicator: Who ls He? - K. Robert Kern; Charles H. Kelly (Journal of Applied Communications, 1974)
The U. S. Agricultural scene is vast and has been explored many times from many angles. The purpose of this study was to describe and analyze an element of agriculture that has gone largely unnoticed and unresearched - the communicator working for an agricultural input company.